Extreme on-demand contactless modulation of elastic properties in magnetostrictive lattices. (1st December 2022) - Singh, A; Mukhopadhyay, T; Adhikari, S; Bhattacharya, B
Abstract: 2D lattices are widely popular in micro-architected metamaterial design as they are easy to manufacture and provide lightweight multifunctional properties. The mechanical properties of such lattice structures are predominantly an intrinsic geometric function of the microstructural topology, which are generally referred to as passive metamaterials since there is no possibility to alter the properties after manufacturing if the application requirement changes. A few studies have been conducted recently to show that the active modulation of elastic properties is possible in piezoelectric hybrid lattice structures, wherein the major drawback is that complicated electrical circuits are required to be physically attached to the micro-beams. This paper proposes a novel hybrid lattice structure by incorporating magnetostrictive patches that allow contactless active modulation of Young's modulus and Poisson's ratio as per real-time demands. We have presented closed-form expressions of the elastic properties based on a bottom-up approach considering both axial and bending deformations at the unit cell level. The generic expressions can be used for different configurations (both unimorph or bimorph) and unit cell topologies under variable vertical or horizontal magnetic field intensity. The study reveals that extreme on-demand contactless modulation including sign reversal of Young's modulus and Poisson's ratio (such as auxetic behavior in a structurally non-auxetic configuration, or vice-versa) is achievable by controlling the magnetic field remotely. Orders of difference in the magnitude of Young's modulus can be realized actively in the metamaterial, which necessarily means that the same material can behave both like a soft polymer or a stiff metal depending on the functional demands. The new class of active mechanical metamaterials proposed in this article will bring about a wide variety of design and application paradigms in the field of functional materials and structures.